Vacancy defect-promoted nanomaterials for efficient phototherapy and phototherapy-based multimodal Synergistic Therapy - Xiong, Xinyu; Wang, Li; He, Shan; Guan, Shanyue; Li, Dawei; Zhang, Mingming; Qu, Xiaozhong (Frontiers in Bioengineering and Biotechnology, 2022)
Phototherapy and multimodal synergistic phototherapy (including synergistic photothermal and photodynamic therapy as well as combined phototherapy and other therapies) are promising to achieve accurate diagnosis and efficient treatment for tumor, providing a novel opportunity to overcome cancer. Notably, various nanomaterials have made significant contributions to phototherapy through both improving therapeutic efficiency and reducing side effects. The most key factor affecting the performance of phototherapeutic nanomaterials is their microstructure which in principle determines their physicochemical properties and the resulting phototherapeutic efficiency. Vacancy defects ubiquitously existing in phototherapeutic nanomaterials have a great influence on their microstructure, and constructing and regulating vacancy defect in phototherapeutic nanomaterials is an essential and effective strategy for modulating their microstructure and improving their phototherapeutic efficacy. Thus, this inspires growing research interest in vacancy engineering strategies and vacancy-engineered nanomaterials for phototherapy. In this review, we summarize the understanding, construction, and application of vacancy defects in phototherapeutic nanomaterials. Starting from the perspective of defect chemistry and engineering, we also review the types, structural features, and properties of vacancy defects in phototherapeutic nanomaterials. Finally, we focus on the representative vacancy defective nanomaterials recently developed through vacancy engineering for phototherapy, and discuss the significant influence and role of vacancy defects on phototherapy and multimodal synergistic phototherapy. Therefore, we sincerely hope that this review can provide a profound understanding and inspiration for the design of advanced phototherapeutic nanomaterials, and significantly promote the development of the efficient therapies against tumor.